Centro de cálculo, redes de circulação e história da geografia: o caso da Revista Brasileira de Geografia do IBGE (1939-1996) - Guilherme Ribeiro; André Santos da Rocha; Leandro Dias de Oliveira; Marcio Rufino Silva; Tatiana Tramontani Ramos; Glauco Bruce Rodrigues; Leonardo Arantes (Confins)
This research project aims to examine, from the point of view of the history of geography, what was the main Brazilian geographic journal of the twentieth century: the Revista Brasileira de Geografia. Organized by the National Council of Geography of the Brazilian Institute of Geography and Statistics, two hundred and thirteen editions were published in the period between 1939 and 1996 involving national and international authors, geographers and non-geographers, and a variety of themes across different historical contexts, political orientations, and epistemological trends. Although since the nineties of the last century the Revista Brasileira de Geografia has been subject of some studies, they are still quite shy compared to its influence. Thus, taking as a methodological reference the concept of centrals of calculation and the related notions of networks and circulation of knowledge elaborated by the French representative of science studies Bruno Latour, the aim of this research is to examine in quantitative and qualitative terms the contribution of the Revista Brasileira de Geografia both for the history of geography and for the understanding of the national territorial reality. Therefore, we selected four axes of analysis: (i) transnational networks and knowledge circulation: the role of translations; (ii) scales of urbanization: the Rio-São Paulo megalopolis; (iii) geopolitics of the environmental issue: Brazilian perspectives; and (iv) social movements, activism and struggles: other agendas.